Experiment of Tamper Detection and Recovery Watermarking in PACS - Siau-Chuin, Liew; Jasni, Mohamad Zain (2010)
Medical images such as x-rays, ultrasounds and MRI (Magnetic Resonance Imaging) plays an important role in helping the physicians to diagnose a disease or body conditions. These images can be tampered with existing image processing tools that is easily available. The usage of security measures such as watermarking can protect the integrity of the images. Numerous watermarking schemes with basic security functions and even tampered image recovery are available. But there is no research on the experimentation of watermarking in the operational environment that involves PACS (Picture Archiving and Communication Systems). This paper will focus on the experiment of selected watermarking scheme running in a simulated operation environment. The watermarked images will be tested to know its effectiveness by comparing its recovery rates.